Pilot study of peer modeling with psychological inoculation to promote coronavirus vaccination. Issue 1 (20th January 2022) - Ramirez, A G; Despres, C; Chalela, P; Weis, J; Sukumaran, P; Munoz, E; McAlister, A L
Abstract: Promoting coronavirus vaccination is deterred by misinformation, ranging from elaborate conspiracy theories about sinister purposes to exaggeration of side effects, largely promulgated by social media. In this pilot study, we tested the effects of different messages on actions leading to vaccination. Two theory-based advertisements were produced for Facebook, which provided video testimonials from peer role models recommending vaccination and its benefits while providing psychological inoculation through the models' acknowledging misinformation, rejecting it and receiving the vaccine. These ads were paid to appear on Facebook users' feeds in rural counties in South Texas, along with a generic vaccine promotion ad from the CDC without peer models or psychological inoculation. Ad viewers could click a link to 'find a vaccine near you'; these responses served as the outcome variable for assessing experimental effects. Ads featuring peer modeling with psychological inoculation yielded a significantly higher rate of positive responses than CDC ads (30.5 versus14.9/1000 people reached in English and 49.7 versus 31.5/1000 in Spanish; P < 0.001 for both English and Spanish rate comparisons). This provides useful pilot data supporting the hypothesis that theory-based communication, i.e. peer modeling with psychological inoculation, may be more effective than more traditional forms of advertising for promoting coronavirus vaccination.